Kinematic subpopulation structure variations in cryopreserved semen from dairy cattle - Solís, Juan M. (2025)
Introduction. In the dairy industry, frozen-thawed semen is crucial for artificial insemination and genetic improvement of cattle. Objective. To evaluate the variation in the kinematic subpopulation structure of frozen-thawed semen in Jersey and Holstein breeds using a CASA-mot system. Materials and Methods. The study was conducted from April to November 2023, at the Animal Reproduction Laboratory (AndroTEC), located at the Campus Tecnológico Local San Carlos, Alajuela, Costa Rica. Eight animals from the Holstein and Jersey breeds were used, and nine doses of frozen-thawed semen per animal were analyzed for each breed. A total of 72 semen doses from eight bulls (four from each breed) were thawed at 37 °C for 30 s. Sperm motility and kinematic variables were analyzed using CASA-mot (Computer-Assisted Semen Analysis) technology. Results. The Jersey breed presented higher percentages of total motile, progressive motile, and rapid spermatozoa compared to the Holstein breed (P < 0.05). Principal component analysis revealed two significant factors explaining 87.5 % of the total variance in kinematic variables. The kinematic variables between sperm subpopulations (SP) showed differences (P < 0.05) in both breeds. Subpopulation SP2 was the fastest, with higher values for curvilinear speed (VCL), straight-line speed (VSL), and average trajectory speed (VAP) in both Holstein and Jersey bulls. Conclusions. Kinematic differences were found between the identified subpopulations in both breeds. The kinematic patterns of the subpopulations present in the ejaculate could influence fertility and reproductive performance.